Analisis Butir Soal untuk Materi Gaya di Sekolah Dasar - Gibta Paskalin; Maria Melani Ika Susanti (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2020)
Item analysis was conducted to assess the quality of items in the style material in grade IV elementary school. To achieve this goal, four points were examined in this study, including (1) item validity, (2) reliability, (3) difficulty level, and (4) item discrimination power. This research is a quantitative descriptive research. The subjects of this study were 27 grade IV students at Kentungan Elementary School in February 2020. Quantitative data analysis techniques were carried out to determine the validity, reliability, difficulty level, and distinguishing features using the SPSS 17 application program. The results of this study were: (1 ) there are 15 valid questions in each cycle, (2) the level of reliability in the high category both in cycle I and cycle II, (3) in cycle I, there are 8 easy questions, 6 medium questions, and 1 difficult problem, whereas in cycle II, there are 8 easy questions and 7 moderate questions, (4) Related to the power of distinguishing questions, in cycle I, there are 8 questions in the excellent category, 6 good questions, and 1 sufficient problem, whereas in cycle II, there are 14 good questions and 1 question is enough. Keywords: item analysis, validity, reliability, item difficulty level, item discrimination power